2011
DOI: 10.1007/s00253-011-3280-9
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Bacillus subtilis for isobutanol production by heterologous Ehrlich pathway construction and the biosynthetic 2-ketoisovalerate precursor pathway overexpression

Abstract: In the present work, Bacillus subtilis was engineered as the cell factory for isobutanol production due to its high tolerance to isobutanol. Initially, an efficient heterologous Ehrlich pathway controlled by the promoter P(43) was introduced into B. subtilis for the isobutanol biosynthesis. Further, investigation of acetolactate synthase of B. subtilis, ketol-acid reductoisomerase, and dihydroxy-acid dehydratase of Corynebacterium glutamicum responsible for 2-ketoisovalerate precursor biosynthesis showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(95 citation statements)
references
References 53 publications
3
92
0
Order By: Relevance
“…B. subtilis shows great promise for producing several of these compounds, since, unlike many other currently used industrial microbes, it naturally imports and metabolizes cellobiose and C 5 sugars (54,55). Moreover, using its robust genetic system, several investigators have already introduced into B. subtilis the relevant metabolic pathways needed to produce some of these compounds (54,(56)(57)(58)(59), which, when paired with the cellulose-degrading system that we have created, should enable the direct production of many valuable biocommodities from biomass.…”
Section: Discussionmentioning
confidence: 99%
“…B. subtilis shows great promise for producing several of these compounds, since, unlike many other currently used industrial microbes, it naturally imports and metabolizes cellobiose and C 5 sugars (54,55). Moreover, using its robust genetic system, several investigators have already introduced into B. subtilis the relevant metabolic pathways needed to produce some of these compounds (54,(56)(57)(58)(59), which, when paired with the cellulose-degrading system that we have created, should enable the direct production of many valuable biocommodities from biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus subtilis is a model Gram-positive organism that is sought after for its capacity in the high-level production of biopolymers (41), metabolites (42), and recombinant proteins (43). In contrast to E. coli, B. subtilis has received a "generally regarded as safe" (GRAS) designation, readily secretes products into the extracellular medium, and can metabolize nearly any carbon source, making it an attractive biomanufacturing platform (43).…”
mentioning
confidence: 99%
“…One major disadvantage of B. subtilis is that it prefers to grow aerobically and is not naturally fermentative, though in certain conditions it can ferment sugars to lactate and 2,3-butanediol (Nakano and Zuber 1998); while it can be modified to produce ethanol (Romero et al 2007), reported levels are rather low (up to 8.9 g/l), insufficient for economical distillation. However, it may be well suited to the production of other classes of product such as isobutanol and other branched chain alcohols, produced via the amino acid biosynthetic pathway rather than via fermentation (Li et al 2011). Thus, B. subtilis may ultimately be the most suitable of the current chassis organisms for recombinant biomass conversion systems.…”
Section: Chassis Considerationsmentioning
confidence: 99%